On the applicability of in situ soil probings to geological analyses - Radaszewski, Robert; Wierzbicki, Jędrzej (Wydawnictwo Naukowe UAM, 2011)
Examples of geoengineering methods (static and dynamic probings) that can be applied to analyses of geological environments are presented. The potential is shown by the results of the determination of the values of the soil-density index (ID), the soil-behaviour index (Ic), the constrained modulus (M), the overconsolidation ratio (OCR) and their vertical changes. The values obtained for ID and Ic facilitate the determination of layers with a specific character. This is demonstrated for several aeolian and glacial deposits in Poland. The application of static probings to the analyses of changes in OCR and M made it possible to identify several depositional phases and the effect of postdepositional processes. Usages of the probings can significantly contribute to the interpretation of palaeo-environments (e.g. in the context of geostatistical models), but the results obtained should be handled cautiously.
Keywords: Dynamic penetration test; Static penetration test; Soil-density index; Overconsolidation ratio